Herpes Zoster and Post-Herpetic Neuralgia—Diagnosis, Treatment, and Vaccination Strategies - Delwyn Zhi Jie Lim; Hong Liang Tey; Brenda Mae Alferez Salada; Jolene Oon; Ee-Jin Darren Seah; Nisha Suyien Chandran; Jiun Yit Pan (2024)
Introduction: Herpes zoster is caused by the reactivation of latent varicella infection within the sensory ganglia, caused by the varicella-zoster virus (VZV). The disease is classically characterized by a painful unilateral vesicular eruption. Complications of the disease include herpes zoster ophthalmicus, Ramsay Hunt syndrome, acute retinal necrosis, and post-herpetic neuralgia. In this paper, we discuss the epidemiology, pathogenesis, clinical features, diagnosis, management, and vaccination strategies of herpes zoster and post-herpetic neuralgia. Method: This paper was developed with input from specialists from Singapore’s public sectors—dermatologists, family physicians, and infectious diseases specialists. Results: The diagnosis of herpes zoster is clinical and can be aided with laboratory investigations. Early initiation of antivirals, within 72 h of onset, can reduce the severity and duration of the condition and decrease the intensity of pain. In patients with a high risk of post-herpetic neuralgia, early initiation of anticonvulsants or tricyclic antidepressants can be considered. Herpes zoster is highly preventable, with the advent of the recombinant zoster vaccine (RZV) providing an overall vaccine efficacy of 97.2%. Procedures such as epidural blocks and subcutaneous or intracutaneous injections of local anesthetics and steroids can be considered for patients with a high risk of post-herpetic neuralgia to reduce its incidence. Conclusion: This article serves as a guideline for clinicians in the diagnosis, investigations, management, and prevention of herpes zoster. With the majority of adults in Singapore currently at risk of developing herpes zoster due to varicella immunization being only introduced in 2020, it is important for clinicians to recognize and manage herpes zoster appropriately.